2015
DOI: 10.1186/s12917-015-0401-1
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiology of Peste des petits ruminants virus infection in Turkana County, Kenya

Abstract: BackgroundPeste des petits ruminants (PPR) is a contagious viral disease of small ruminants. Serum samples from sheep (n = 431) and goats (n = 538) of all ages were collected in a cross-sectional study in Turkana County, Kenya. The objective was to estimate the sero-prevalence of PPR virus (PPRV) infection and associated risk factors in both species.PPRV competitive enzyme-linked immuno-sorbent assay (c-ELISA) analysed the presence of antibodies in the samples. All analyses were conducted for each species sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…In Kenya, the Turkana region located in the north-western part of the country is identified as high risk: in 2011 in this area, PPRV Lineage III was detected from tissue samples collected from goats suspected of having died of PPR (45). The results of a seroprevalence study showed that 40% of the sheep (n = 431) and 32% of the goats (n = 538) sampled were seropositive (46). In 2016, PPR occurrence was confirmed in both camels and goats in the second main area identified at risk by our model, i.e., the north-eastern part of the country including Mandera, Wajir, Isiolo, and Marsabit districts (22).…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya, the Turkana region located in the north-western part of the country is identified as high risk: in 2011 in this area, PPRV Lineage III was detected from tissue samples collected from goats suspected of having died of PPR (45). The results of a seroprevalence study showed that 40% of the sheep (n = 431) and 32% of the goats (n = 538) sampled were seropositive (46). In 2016, PPR occurrence was confirmed in both camels and goats in the second main area identified at risk by our model, i.e., the north-eastern part of the country including Mandera, Wajir, Isiolo, and Marsabit districts (22).…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases pose a serious threat to these livestock. For example, the 2007 PPR outbreak caused an estimated 19.1 million USD in losses in Turkana and spread out to other ASALs in Kenya (FAO 2009;Kihu et al 2015a). In 2015, the PPR seroprevalence in Turkana was estimated at 40% and 32% in goats and sheep, respectively (Kihu et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of PPR infection is based on four fundamental principles, namely virus isolation, antigen detection, nucleic acid detection and antibody identification from serum with sequencing. The ELISA test is widely used in field studies (Balamurugan et al, 2012;Kihu et al, 2015). Virus isolation and neutralization tests in cell cultures are time-consuming, costly and not very productive.…”
Section: Advances In Animal Andmentioning
confidence: 99%